EmpowErmEnt dan Job InvolvEmEnt Pengaruhnya terhadaP Job SatISfactIon dan EmployEE pErformancE (Study Pada KoPerasi graha santi – sanur) - Ni Kadek suryani; I Wayan gde sarmawa (Forum Manajemen STIMI Handayani Denpasar, 2014)
Employees of a company are not an expenses but it is a corporate assetthat must be managed to be able support the organization to achieve its goals.Therefore, employees should be empowered through their engagement as much aspossible in different things in the company, especially on the planning, decisionmaking,implementationandevaluationaswellastakingtheproperstepstodealingwith the problems in their job responsibilities. Provide authority and greater involvement to employees is expected to foster a sense of satisfaction, thus indicatingfor better performance.This research aimed to conduct a study in effect of empowerment and job involvementon job satisfaction and employee performance at Koperasi Graha Santi Sanur. Thenumber of all employees to be respondents is 40 people. The data is processed byPartial Least Square Structural Equation Modeling (PLS-SEM), and the result isfound that the empowerment and job involvement of employees showed a positiveand significant effect on job satisfaction and employee performance.